2016
DOI: 10.1183/13993003.00458-2016
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with undiagnosed and overdiagnosed COPD

Abstract: Worldwide, studies have shown that about 60-86% of people with chronic obstructive pulmonary disease (COPD) have not been diagnosed, which represents a missed opportunity to decrease disease burden through optimal management, including smoking cessation support and prescription medications [1][2][3]. Overdiagnosed COPD is also common, with prevalence estimates ranging from 4% to 64% in the general population and primary care settings [4,5]. Overdiagnosis can lead to unnecessary COPD treatments with their own r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…The diagnosis of COPD in subjects without spirometric evidence of airflow obstruction is common in primary care. 29 As such, we consider that our results reflect the reality of COPD management in primary care and further support the importance of the use and appropriate interpretation of spirometry in the diagnosis of COPD. On the other hand, we have demonstrated that education programs by trained health-care professionals, acting as case manager, are feasible to implement in FMCs.…”
Section: Discussionsupporting
confidence: 76%
“…The diagnosis of COPD in subjects without spirometric evidence of airflow obstruction is common in primary care. 29 As such, we consider that our results reflect the reality of COPD management in primary care and further support the importance of the use and appropriate interpretation of spirometry in the diagnosis of COPD. On the other hand, we have demonstrated that education programs by trained health-care professionals, acting as case manager, are feasible to implement in FMCs.…”
Section: Discussionsupporting
confidence: 76%
“…Young and colleagues [49] argued for a widespread use of spirometry screening for airflow obstruction in asymptomatic smokers, in an attempt to appropriately evaluate the prevalence of COPD and detect individuals at an increased risk for lung cancer early. Some identified determinants of under-diagnosed COPD include male sex, lower level of education, being of ethnic minority, and lower comorbidity burden [45, 46, 50], while younger age, being overweight, and higher levels of comorbidities are risk factors for COPD misdiagnosis [5052]. Therefore, individuals with these characteristics should be offered spirometry for a correct diagnosis of COPD, which in turn will allow for further risk stratification in lung cancer screening [53].…”
Section: Lung Cancer Screening Strategy Incorporating Copdmentioning
confidence: 99%
“…The largest contribution of COLD/Can-COLD-related publications may be seen to have advanced knowledge and understanding surrounding appropriate diagnostic approaches and disease characterisation with impact on recommendations for health care services and interventions. More specifically, the larger proportion of studies to date have served to appropriately quantify COPD prevalence and disease determinants 3,4 spirometry testing and prediction equations [5][6][7][8][9] , diagnosis performance and early detection [10][11][12][13][14][15] , novel methods of assessing COPD 16,17 , and COPD clinical impact [18][19][20][21][22] . Consequently, we have elected for this manuscript to summarise key learnings from the CanCOLD study that are relevant to the primary care setting.…”
Section: Resultsmentioning
confidence: 99%